2020
DOI: 10.15414/jmbfs.2020.9.4.823-830
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Functional and Sensory Properties of Acha-Tamba Based Ogi Enriched With Hydrolysed Soy Peptides

Abstract: The physicochemical, functional and sensory properties of acha-tamba based ogi enriched with hydrolyzed soy peptides were investigated. The proximate value moisture content increased with percentage inclusion of acha tamba and peptides additions (10.1-11.5) % Similar trend were observed in protein values (2.15-8.02) %, Ash (3.05-3.34) %, crude, fiber (7.05-10.6) % and carbohydrate content 65.9-69.2) % which had down tail trends on acha ,tamba and peptides percentage inclusions. Water absorption capacity (1.07-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…The percent protein content of the ogi samples was observed to be higher in 100% maize ogi compared with the other blends, which had lower protein contents, as a decrease in the protein content was observed as the level of millet increased in the blends. Moreover, the protein content (9.19-10.05%) obtained in this study is comparatively higher than the 2.15-8.02% reported for ogi produced from acha ogi enriched with hydrolyzed soy peptides (Hleba, 2020) [8] . This implies that the ogi samples produced in this study may be useful in the management of protein-energy malnutrition (Ijarotimi et al, 2021) [10] .…”
Section: Discussioncontrasting
confidence: 74%
“…The percent protein content of the ogi samples was observed to be higher in 100% maize ogi compared with the other blends, which had lower protein contents, as a decrease in the protein content was observed as the level of millet increased in the blends. Moreover, the protein content (9.19-10.05%) obtained in this study is comparatively higher than the 2.15-8.02% reported for ogi produced from acha ogi enriched with hydrolyzed soy peptides (Hleba, 2020) [8] . This implies that the ogi samples produced in this study may be useful in the management of protein-energy malnutrition (Ijarotimi et al, 2021) [10] .…”
Section: Discussioncontrasting
confidence: 74%
“…Fonio and fonio starch have been used in various food and nonfood applications (Table 2). Food applications include producing sprouts and malts (Ayo, Agbatutu, & Iribom, 2019; Lasekan, Salva, & Abbas, 2010; Nzelibe & Nwasike, 1995; Nzelibe, Obaleye, & Onyenekwe, 2000), gluten free drinks (Badejo et al., 2017), infant weaning and children's foods (Agbede, Omotoso, Oloruntola, Ayeni, & Aletor, 2019; Sosanya, Nweke, & Ifitezue, 2018), breakfast cereals (Mbaeyi‐Nwaoha & Uchendu, 2016), nonwheat pasta, noodles, porridge, puddings, crackers, biscuits and cookies, cakes, and sourdough breads (Ayo & Ayo, 2018; Ayo et al., 2019; Chinma, Ihekoronye, Mukoro, & Eke, 2015; Coda et al., 2010; Edema, Emmambux, & Taylor, 2013; McWatters, Ouedraogo, Resurreccion, Hung, & Phillips, 2003; Meli et al., 2013; Ogori, Uzor, Hleba, Císarová, & Glinushkin, 2020; Olagunju, Omoba, Enujiugha, & Aluko, 2018; Raji, Nassam, Abolaji, Ayorinde, & Raji, 2018; Umerie & Umeh, 2016). From the results summarized in Sections 2 and 3, it is concluded that fonio grain and flour do not contain gluten‐type protein for desired rheology for a range of bakery products.…”
Section: Food and Other Applications Of Fonio And Fonio Componentsmentioning
confidence: 99%
“…Fonio flour was mixed with other flours/ingredients to improve the nutritional and/or textural quality of different food products (Agbede et al., 2019; Agu, Ayo, & Jideani, 2015; Agu, Ezeh, & Jideani, 2014; Agu, Jideani, & Yusuf, 2007; Ayo & Ayo, 2018; Ayo & Gidado, 2017; Ayo et al., 2019; Chinma et al., 2015; Ishola, Ojokoh, & Odesanya, 2018; Jideani, Alamu, & Jideani, 2007; Jideani, Salami, & Jideani, 2008; Mbaeyi‐Nwaoha & Uchendu, 2016; Ogori et al., 2020; Olagunju et al., 2018; Sosanya et al., 2018).…”
Section: Food and Other Applications Of Fonio And Fonio Componentsmentioning
confidence: 99%
See 2 more Smart Citations